Constraining millennial‐scale changes in northern component water ventilation in the western tropical South Atlantic - Campos, Marília C.; Bahr, André; Kuhnert, Henning; Portilho‐Ramos, Rodrigo C.; Mulitza, Stefan (Paleoceanography and paleoclimatology, 2020)
The highest mid‐depth negative δ13C excursions occurred in the western tropical South Atlantic and dissipated further south - Reduced Northern Component Water ventilation in the western tropical Sout...
Gesehen am 21.10.2020